Ways of forming the reading interests of younger students (Pedagogy of Higher and Secondary Education, 2012)
Kompaniy O. V. Ways of forming the reading interests of younger students.The author investigates the definition of theoretical knowledge, defines the abilities, characterizes exercises and stages, which promote the awakening of readers' interests.
Keywords: exercises (preparatory-motivating, reproductive, informative, creative, testing) and stages of teaching (motivation and orientation; comprehension of literary work; text analysis; consolidation)